The improved clinical course of persistent tachypnea of infancy with inhaled bronchodilators and corticosteroids. Issue 12 (21st September 2021) - Marczak, Honorata; Peradzyńska, Joanna; Seidl, Elias; Griese, Matthias; Urbankowski, Tomasz; Lange, Joanna; Bogusławski, Stanisław; Krenke, Katarzyna
Abstract: Background: Persistent tachypnea of infancy (PTI) is the most common interstitial lung disease in young children. As no standardized therapeutic guidelines exist, different pharmaceuticals are used to treat PTI; inhaled corticosteroids (ICS) and bronchodilators being mostly used. This observation assessed the effectiveness of bronchodilators and ICS in children with PTI enrolled in the children's interstitial lung diseases (chILD)‐EU Register. Methods: Symptomatic children with PTI were observed according to a predetermined stepwise protocol including bronchodilators as the first choice treatment (6 weeks). In patients with incomplete response, additionally,  ICS was given (12 weeks). Signs, symptoms, and pulmonary function were evaluated at three time points: at baseline, 6 (±1) weeks after initiation of bronchodilators, and 12 (±1) weeks after bronchodilators/ICS. Results: Thirty‐one children (median age: 44 months, interquartile range [IQR]: 15–67) were included. The therapy was associated with a significant reduction of tachypnea (53.3% of patients, p  = 0.02), exercise intolerance (52.2% of patients, p  < 0.001), chest retractions (43.8% of patients, p  = 0.04), and crackles (29.2% of patients, p  = 0.02). Also, a significant improvement in forced expiratory volume in 1 s (FEV1 ) (median z score: −2.21 vs. −0.47, p  = 0.03), residual volume (RV) (median z score 5.28 vs. 1.07, p  = 0.007), RV% total lung capacity (TLC) (median z score: 6.05 vs. 1.48, p  = 0.01), sRaw (median z score: 6.6 vs. 4.64, p  = 0.01), R5 (median z score: 1.27 vs. 0.31, p  = 0.009), and R5–R20 (median: 0.58 vs. 0.26 kPa/(l/s), p  = 0.002) was demonstrated. Conclusions: Inhaled bronchodilators and ICS may exert a positive effect on the severity of symptoms and pulmonary function test (PFT) in symptomatic children with PTI. However, a randomized control trial should be conducted to confirm their effectiveness.